1991
DOI: 10.1001/archderm.1991.01680010101017
|View full text |Cite
|
Sign up to set email alerts
|

Impetigo Herpetiformis Associated With Hypocalcemia of Congenital Rickets

Abstract: A 30-year-old woman with congenital rickets and autosomal recessive ichthyosis developed impetigo herpetiformis in the second trimester of her first pregnancy. This condition was temporally related to her discontinuation of vitamin D supplements and subsequent hypocalcemia. No associated systemic symptoms were observed, and a healthy baby was delivered prematurely at 34 weeks' gestation. This report supports the association between hypocalcemia and impetigo herpetiformis and raises theoretical questions regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In our literature review, it is confirmed that IH is a notorious skin disorder of pregnancy with increased morbidity and mortality that affects both the mother and the fetus [1,2]. IH mainly afflicts pregnant women during the third trimester of pregnancy but it may also occur in the first trimester of pregnancy, puerperium or menstrual period, and it may even occur in men [8,11,12,13,14]. In patients who suffered from IH before, the disease recurs at an earlier gestational age during a subsequent pregnancy [7,9,10].…”
Section: Discussionmentioning
confidence: 95%
“…In our literature review, it is confirmed that IH is a notorious skin disorder of pregnancy with increased morbidity and mortality that affects both the mother and the fetus [1,2]. IH mainly afflicts pregnant women during the third trimester of pregnancy but it may also occur in the first trimester of pregnancy, puerperium or menstrual period, and it may even occur in men [8,11,12,13,14]. In patients who suffered from IH before, the disease recurs at an earlier gestational age during a subsequent pregnancy [7,9,10].…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that IH is not confined to pregnancy. Some case reports indicate that hypocalcaemia and oral contraceptive hormones can induce IH in susceptible subjects 2–5 . Its clinical and histological features are identical with generalised pustular psoriasis (GPP).…”
Section: Discussionmentioning
confidence: 99%
“…In one report, only five of 57 patients were found to have hypocalcaemia and it has been claimed that the condition develops secondarily to malabsorption or hypoalbuminaemia 10,11 . The physiological decrease of total serum calcium levels by 5–6% during pregnancy may be another contributory factor 4,10 . But one case report indicated that hypocalcaemia was a causative factor in the development of IH in a pregnant woman with congenital rickets, because she recovered with only oral calcitriol and topical steroid therapy 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides other causes of a disseminated spread of pustules and blisters, differential diagnosis includes also impetigo herpetiformis, of which nearly 100 cases have been reported until now. This disease has been observed in pregnancy with and without hormonal dysregulations [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14]. In the more recent literature, this disease is considered to be a generalized manifestation of pustular psoriasis [5, 6, 14].…”
Section: Introductionmentioning
confidence: 99%